PENGELOLAAN KEGIATAN EKSTRA KURIKULER DALAM UPAYA PENGEMBANGAN KECERDASAN EMOSIONAL PESERTA DIDIK DI MA SUMBER BUNGUR PAKONG - Saiful Hadi; Anis Fitriya (re-JIEM (Research Journal of Islamic Education Management), 2018)
Emotional intelligence form a certain ability the can possession by someone for can supervision feeling the be found inside self. Managemen extracurricular activity is a cartain exertion the did by all sorts of side institute inside planning, actuating, controlling, and evaluating activity the be outer part o’clock lesson or outer part class, where conducted activity talked about be able take elong change the carrefully concerning development personality an individual the follow it. Inside research this approachment the purpose because of researcher is approachment qualitative. Product research the result of development emotional intelligence student town managemen extracurricular activity in MA Sumber Bungur Pakong year lesson 2017-2018 that is development talked about alredy did by all sorts of side institude included builder extracurrucular activity be present. see extracurrucular in MA Sumber Bungur Pakong the be able develop emotional intelligence student that is only be found some extracurricular antivity certain that is extracurricullar scouting, adolescent red cross, and FLP (magazine school). Which person each and avery extracurricular talked about a builde activity have manner self inside development emotional intelligence student the participate in within. See development the did by builde town manajegemen extracurricular activity scouting that is: fulfillment SKU, fulfillment TKK, and conducted coarching LDK. See inside adolescent red cross activity, development the did by a builder that is: accompanying go along students become the member inside activity free therapy, activity assist calamity world, and give assist see fatherless child and poor. Whereas insid activity FLP, development the did by a builder FLP that is: observation about all sorts of work scientific, gift leadership special inside presentation, and notify along with know various opus the result by seniors.